Expert system on crop ecology adviser / Joyce Jessica Michael Gumpil - Joyce Jessica, Michael Gumpil (2002)
The title of this project is crop ecological adviser (CEA) system. It is an expert system project written using the Visual Prolog 5.2 language. CEA intended to help farmers by giving recommendations to them on the list of crops that are suitable to be planted on his area based on the ecological factors in his place. The factors include mean temperature, rainfall per annum and soil. The system can provide explanation on why certain crops are recommended instead of others. By this, the system can aid in making decision on which crop can be cultivated on his land based on the recommendations. Apart from that, the system can also provide explanation on how it derives the conclusion. If a farmer had grown crops, then he can use this system to determine the suitability of the crop planted on his land. CEA system is able to give explanation to user why certain crops are not suitable to be planted in an area. CEA system is developed using rule-based approach. This approach is a benefits because the rules can be added and modified anywhere in the knowledge base. Furthermore, the changes here do not affect the control mechanism of CEA system. The inference engine strategy used in CEA is the forward chaining. It gathers data from system user and from there it will infer what can be concluded from it. CEA offers advantages and limitations. Advantages of it can be seen from developer perspective - ease of rule addition and modifiability and explanation - how facilities can help to understand the processing of CEA - and from end-user perspective - justification of its recommendation, user friendly system, cater for crops scientific names, range values usage for ecology factors and more than one recommendation to help farmers diversify crops in his or her area. However, CEA only caters for ecology factors, can be slow, rules require exact matching and exact information are the main drawbacks of CEA. Further works for CEA include additional rules not only from ecology perspective but also from the aspect of crop management, fertilizers and pesticides management.